The mediating effect of electronic information system on the relationship between administrative control and employees' performance in Jordanian industrial companies - Al-Ganhreh, Emad Abed Abdullah
Previous studies and practical applications have proven that th companies that used administrative control have achieved an enhanced performance of their employees. The problem statement of the study is based on the absence of administrative control in Jordanian industrial companies. There were reports of violations of official conducts at" work by employees at the administrative levels whereby they wasted the official time for informal activities during the working hours. This misconduct is adversely affecting the organizations' performance and the achieved goals. The Employees' performance can be improved by implementing strategic administrative control through the application of electronic information system in all sections of the organization. Therefore, the main objective of this study aims to examine the effects of electronic information system as mediating variable between the administrative control and the employees' performance in Jordanian industrial companies. This study collected data through the survey questionaires in which 376 sampled employees from seven industrial companies in Jordan provided responses used as data for the study. The sample comprises of departmental managers, departmental heads and human resources employees. This study used the Structural Equation Modelling (SEM) using IBM - SPSS - AMOS 24.0 for data analysis. Th validity and reliability of the measurement and the structural models were confirmed. The results showed that transparency and control systems, as dimensions of administrative control and information system, positively affected employees' performance, while administrative leadership has no effects on employees' performance, The results also showed that a mediating effect of the electronic information systems is a positive factor n the relationship between administrative control and employees' performance. This study concluded that Jordanian industrial companies must "adopt administrative control through the application of electronic information system in order to impro e the performance of employees and increase their efficiency. The study is significant as it can help companies achieve their visions, mission, and goals, while facilitating the process of identifying obstacles that faced the execution of administrative control, employees' performance, and the importance of electronic information systems as corrective measure. It is therefore, recommended that Jordanian industrial companies can enhance employees' awareness of the the importance of the concept of transparency in order to increase organizational goals as well as preserving employees' appraisal for integrity and promotion. Jordanian industrial companies also should maintain the democratic style of leadership, thus increasing leaders' focus on their subordinates, motivate them to feel as owners of the organization. That motivation would lead to efficient service delivery. Finally, Jordanian industrial companies should facilitate access to information for all employees through the establishment of electronic information system department that provides the employees with the required information rapidly and effectively.